1999
DOI: 10.1111/j.1945-5100.1999.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering on the Moon: Patina on Apollo 17 samples 75075 and 76015

Abstract: Abstract-We studied patinas on lunar rocks 75075 and 76015 from the Apollo collection using a multidisciplinary approach, including scanning electron microscopy (SEM), energy dispersive x-ray spectrometry (EDS), transmission electron microscopy (TEM), wavelength-dispersive x-ray (WDS) mapping, M6ssbauer spectroscopy, spectral reflectance, and microspectrophotometry. Based on SEM petrography, we have defined three textural types of patina: glazed, fragmental, and classic (cratered). The presence of classic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 8 publications
0
37
0
1
Order By: Relevance
“…McKay et al, 1991);(b) individual grain effects (such as rare gas implantations and glass splashes); (c) and nanometer-scale particles of metallic iron (npFe 0 ) implanted within agglutinates and as spatter on individual soil grains (Baron et al, 1977;Grant, 1975, 1977;Hapke, 1973;Hapke et al, 1975). Nanophase iron is found in two distinct size ranges which affect the regolith's optical properties differently: (1) npFe 0 , present as thin patinas on irradiated grain rims, is on average about 3 nm in diameter (range between 1 to 15 nm; Keller et al, 1998;Keller and Clemett, 2001;Wentworth et al, 1999) and it is linked to the increase in spectral reflectance in the NIR (e.g. Cassidy and Hapke, 1975;Morris, 1980), a phenomenon often referred to as the 'reddening of the continuum slope'; (2) larger nanospheres up to several hundred nanometres (Housley et al, 1973;James et al, 2002;Keller and Clemett, 2001), which are found in agglutinates: their accumulation with time is linked to soil darkening and consequent weakening of spectral features.…”
Section: The Optical Properties Of the Lunar Surface Materialsmentioning
confidence: 99%
“…McKay et al, 1991);(b) individual grain effects (such as rare gas implantations and glass splashes); (c) and nanometer-scale particles of metallic iron (npFe 0 ) implanted within agglutinates and as spatter on individual soil grains (Baron et al, 1977;Grant, 1975, 1977;Hapke, 1973;Hapke et al, 1975). Nanophase iron is found in two distinct size ranges which affect the regolith's optical properties differently: (1) npFe 0 , present as thin patinas on irradiated grain rims, is on average about 3 nm in diameter (range between 1 to 15 nm; Keller et al, 1998;Keller and Clemett, 2001;Wentworth et al, 1999) and it is linked to the increase in spectral reflectance in the NIR (e.g. Cassidy and Hapke, 1975;Morris, 1980), a phenomenon often referred to as the 'reddening of the continuum slope'; (2) larger nanospheres up to several hundred nanometres (Housley et al, 1973;James et al, 2002;Keller and Clemett, 2001), which are found in agglutinates: their accumulation with time is linked to soil darkening and consequent weakening of spectral features.…”
Section: The Optical Properties Of the Lunar Surface Materialsmentioning
confidence: 99%
“…Transmission electron microscope (TEM) images have revealed the details of npFe 0 layering along the rims of lunar soil grains (e.g., McKay, 1993, 1997;Wentworth et al, 1999). The simulation of micrometeorite bombardment has been proven to form a vapor-deposited layer containing npFe 0 particles (Sasaki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although the production of amorphous rims on lunar soil grains had long been assumed to be a result of solar-wind irradiation damage (23), recent investigations using transmission electron microscopy have revealed that rims of soil grains are not homogeneous and contain a variety of different morphologies and chemical compositions (5). It has been shown that vapor deposition on individual soil grains probably plays a major role compared with the solar-wind sputtering and ion damage in producing the ubiquitous patinas and rims that contain silicarich, amorphous glass with embedded np-Fe 0 (5,14,21). Similarly, a larger proportion of the np-Fe 0 signal in the lunar soil, in particular, in the finest size fractions, is attributed to the surface-correlated, vapor-deposited np-Fe 0 , which increases as the surface area to volume ratio increases (24).…”
Section: Formation Of Nano-phase Metallic Fementioning
confidence: 99%